2023
DOI: 10.18863/pgy.1227948
|View full text |Cite
|
Sign up to set email alerts
|

Erkeklik ve Psikolojik Yardım Arama: Sosyal Kimlik Kuramı Temelli Bir Derleme

Abstract: To improve their quality of life and mental health, people need psychological help. Past research revealed that although participants reported low levels of life satisfaction, they were hesitant to seek psychological help. In the literature, this situation has been defined as mental health treatment gap. In this context, research focuses on reducing the treatment gap by identifying factors that facilitate and hinder seeking psychological help. Many studies consistently report that men are more reluctant to see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Identity is presented as a cognitive system that regulates behavior under relevant conditions (Akdemir, 2018;Caza, Vough, & Puranik, 2018;Walker, 2022). Based on the review of studies by Kantar and Yalcin (2023), the characteristics of this concept can be identified. Durkheim, in particular, raises the question of the mechanisms by which social identity is formed and the influence of individuals' affiliations with different groups.…”
Section: Definition Of the Term Identitymentioning
confidence: 99%
“…Identity is presented as a cognitive system that regulates behavior under relevant conditions (Akdemir, 2018;Caza, Vough, & Puranik, 2018;Walker, 2022). Based on the review of studies by Kantar and Yalcin (2023), the characteristics of this concept can be identified. Durkheim, in particular, raises the question of the mechanisms by which social identity is formed and the influence of individuals' affiliations with different groups.…”
Section: Definition Of the Term Identitymentioning
confidence: 99%